Investigate of Physicochemical and Microbiological Quality of Yenice-Davutköy (Çanakkale) Irrigation Ponds - Kahraman selvi; Seda Özdikmenli Tepeli; Burcu İleri; Ramazan Yıldız; Mehmet Ali Yücel (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study is to determine seasonally water quality characteristics irrigation ponds. Surface water samples were collected from three different sampling points in Yenice and Davutköy irrigation ponds (NW Turkey) for four different seasons. The parameters of dissolved oxygen, pH, salinity, electrical conductivity, chemical oxygen demand, biochemical oxygen demand, ammonium, nitrite, nitrate, total hardness, chloride and sodium adsorption rate (SAR) were investigated for Yenice and Davutköy irrigation water quality. According the national and international water quality standards, physicochemical parameters were determined under permissible level. In addition, sampling ponds are located C1−S1 class of ABD salinity diagrams. This result means that salinity and sodium values of water are suitable for ecological system and can be using for irrigation. Furthermore, the microbial quality of irrigation water for the ponds were determined that rate of mesophyll and psychotropic bacteria are connected with temperature. It is detected that the term of low temperature is high level of psychotropic bacteria and the term of high temperature increase the number of mesophyll bacteria. Pearson correlation analysis between the results of the statistical psychotropic aerobic count and temperature significant was found a strong negative correlation (r= -0,635). Fecal pollution indicator as the number of E.coli stations in Davutköy pond in the summer sampling were determined 110 cfu/100ml and 50 cfu/100ml, respectively. E.coli was not detected other stations and sampling time. Finally, according to obtained analysis results are determined that water qualities for Yenice and Davutköy ponds are suitable for agriculture activities.